2019
DOI: 10.1016/j.pocean.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Fish aggregating devices drift like oceanographic drifters in the near-surface currents of the Atlantic and Indian Oceans

Abstract: Knowledge of ocean surface dynamics is crucial for oceanographic and climate research. The satellite-tracked movements of hundreds of drifters deployed by research and voluntary observing vessels provide high-frequency and high-resolution information on near-surface currents around the globe. Consequently, they constitute a major component of the Global Ocean Observing System (GOOS). However, maintaining this array is costly and in some oceanic regions such as the tropics, spatio-temporal coverage is limited. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Using time-evolving velocity fields from a high resolution ocean circulation model, large numbers of virtual particles with float characteristics that mimic dFADs can be seeded into the simulated ocean to quantify the possible pathways of these floating objects. Such simulations have been used to understand many aspects of ocean circulation and to investigate the connectivity of passively drifting larvae 20 , nutrient flow 21 , marine plastics 22 , non-passive agents such as tuna themselves 23 , as well as dFADs 24 . In the context of dFAD beaching, Lagrangian particle simulation experiments can provide an independent estimate of the broad-scale probability distribution of connectivity between the ocean and beaching events.…”
Section: Introductionmentioning
confidence: 99%
“…Using time-evolving velocity fields from a high resolution ocean circulation model, large numbers of virtual particles with float characteristics that mimic dFADs can be seeded into the simulated ocean to quantify the possible pathways of these floating objects. Such simulations have been used to understand many aspects of ocean circulation and to investigate the connectivity of passively drifting larvae 20 , nutrient flow 21 , marine plastics 22 , non-passive agents such as tuna themselves 23 , as well as dFADs 24 . In the context of dFAD beaching, Lagrangian particle simulation experiments can provide an independent estimate of the broad-scale probability distribution of connectivity between the ocean and beaching events.…”
Section: Introductionmentioning
confidence: 99%
“…In order to keep simulations simple, and considering that the depth of submerged appendages is only available for around 20% of the associated sets in the observer data, an average length of 50 m was assumed for dFAD appendages. However, Imzilen et al (2019) demonstrated a difference in drifting behaviour between dFADs drogued at different depth. In particular, it was found that dFADs in the Atlantic Ocean, up to 80 m deep, drifted slower than drifters used in oceanographic experiments, while those from the Indian Ocean (50-60 m) had similar drift pattern.…”
Section: Sensitivity To Ocean Productsmentioning
confidence: 88%
“…Drogued floating objects such as dFADs are largely driven by surface ocean currents (Imzilen et al 2019). The upper ocean circulation can be separated into (1) near surface Ekman flow in the upper tens of meters, directly generated by surface winds;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a novel approach for estimating the proportion of time silky sharks spend associated with floating objects is proposed. Recently, Imzilen et al (2019) showed that FADs drifted identically to oceanographic drifters, i.e. followed the ocean near‐surface currents.…”
Section: Introductionmentioning
confidence: 99%